Corporate strategies for the Philippine Fisheries Development Authority - Anopol, Ma. Luisa S. (Animo Repository, 1997)
This strategic Management Study was conducted on the PHILIPPINE FISHERIES DEVELOPMENT AUTHORITY (PEDA), a government corporation attached to the Department of Agriculture. By virtue of Presidential Decree No 977 as amended by Executive Order Nos. 772 and 965, PFDA is mandated to promote the development of the fisheries sector and improve efficiency in the handling, preserving, marketing, and distribution of fish and fishery/aquatic products through the establishment and efficient operation of fish ports, fish mistakes, and other marketing facilities.